2013
DOI: 10.1016/j.febslet.2013.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Excision of 8‐oxoguanine from methylated CpG dinucleotides by human 8‐oxoguanine DNA glycosylase

Abstract: CpG dinucleotides are targets for epigenetic methylation, many of them bearing 5-methylcytosine (mCyt) in the human genome. Guanine in this context can be easily oxidized to 8-oxoguanine (oxoGua), which is repaired by 8-oxoguanine-DNA glycosylase (OGG1). We have studied how methylation affects the efficiency of oxoGua excision from damaged CpG dinucleotides. Methylation of the adjacent cytosine moderately decreased the oxoGua excision rate while methylation opposite oxoGua lowered the rate of product release. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
0
14
2
Order By: Relevance
“…Because of this increased DNA damage and decreased repair, S326C- Ogg1 carriers may have an increased potential for cancer development under oxidative stress by a mechanism such as the one proposed in Figure 4. Our findings stand in contrast to studies showing that the S326C-OGG1 variant has constitutively reduced activity compared to the WT protein (23,28,29). The results of this study do not contradict recent findings that S326C-OGG1 undergoes aggregation in vivo under conditions of oxidative stress (48).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Because of this increased DNA damage and decreased repair, S326C- Ogg1 carriers may have an increased potential for cancer development under oxidative stress by a mechanism such as the one proposed in Figure 4. Our findings stand in contrast to studies showing that the S326C-OGG1 variant has constitutively reduced activity compared to the WT protein (23,28,29). The results of this study do not contradict recent findings that S326C-OGG1 undergoes aggregation in vivo under conditions of oxidative stress (48).…”
Section: Discussioncontrasting
confidence: 99%
“…However, such dimerization has yet to be demonstrated under conditions of physiologically relevant oxidative stress, and thus the mechanism of Cys326 oxidation resulting in loss of activity is still unclear. In contrast, several studies indicate that S326C-OGG1 enzymatic activity is equivalent to that of WT OGG1 (25-27), while others have reported constitutively reduced activity in the variant OGG1 (23,28,29). While the methodologies employed in such studies vary, each used purified enzymes under conditions that may alter the redox status of S326C-OGG1.…”
Section: Introductionmentioning
confidence: 87%
“…By adding APE1 and 5 mM MgCl 2 to the reaction mixture, the OGG1 activity for the 5Ј-C:G substrate was increased 6-fold, suggesting that the OGG1 product binding was weaker in the presence of APE1. In contrast to a recent report (54), an adjacent 5-mC:G base pair did not affect the APE1-mediated stimulation of OGG1 (Fig. 5B).…”
Section: C/g-8-oxog/c) B 5ј-t:g (Ie T/g-8-oxog/c) C 5ј-thf:g (Icontrasting
confidence: 99%
“…Critically, G to T transversions occur under oxidative stress conditions in the sequence context of methylated CpG dinucleotides (40), implying formation of unrepaired 8-oxoG at these sites. A recent study also discussed the possibility of reduced repair efficiency of 8-oxoG at the methylated CpG dinucleotide (54). It is also noted that reactive oxygen species-induced G to T transversions have been found in the CpG sequence contexts in carcinoma cells (58).…”
Section: Discussionmentioning
confidence: 99%
“…However, they have suggested that the oxidation of either a single guanine into 8-oxoguanine (8-oxo-G) or 8-oxo-dG or 5-mC into 5-hydroxymethylcytosine (5-hmC), both adjacent to CpG sites, is crucial for the binding of proteins involved in the condensation and inactivation of chromatin (Valinluck et al, 2004) and for the binding of transcription factors to DNA (Zawia et al, 2009). Moreover, the last group and Kasymov et al (2013) reported that the methylation of a cytosine adjacent to an oxidized guanine (8-hydroxy-2'-deoxyguanosine, 8-OHdG) in CpG sites not only synergistically decreases Ogg1 gene expression but also impairs the ability of OGG1 protein to repair the oxidative damage. Finally, ROS might induce sitespecific hypermethylation via the upregulation of DNMT expression or by increasing the formation of DNA methyltransferase (DNMT) complexes (Wu and Ni, 2015).…”
Section: Discussionmentioning
confidence: 99%